The Impact of Spirituality on Wellness for Appalachian Older Adults. Issue 2 (October 2016) - Linscott, Jamie; Randolph, Amber L.; Mayle, Tony
Abstract : The authors examined the role spirituality can play as a protective factor in the wellness of older adults residing in the Appalachian region of the United States. Analysis of participants' interviews identified 4 themes. These themes and implications for counselors working with Appalachian older adults are discussed.